Estrategias activas en el proceso de enseñanza y aprendizaje en el área de lengua y literatura - Iza Toapanta, Adriana Elizabeth (2021)
Education is a gradual process that transfers a set of knowledge, values and skills in the human being, so teachers are those who must be in constant training, in order to develop Critical and Reflective Thinking in students. Therefore, the aim of this research study was to propose active strategies through a didactic guide for the improvement in teaching and learning process in the Language and Literature area, fifth-grade students of “Loja” Elementary School. Regarding the study, it was evidenced that the strategies applied by the teacher do not respond to the students’ needs, since it causes traditional learning by focusing on the content memorization. The qualitative methodology was applied because the educational reality in the didactic process was described. The observation technique allowed collecting relevant data on strategies applied in the teaching-learning process, obtaining the information of the class through the observation guide instrument. Concerning the results, a didactic guide about active strategies in the teaching and learning process of the Language and Literature area was elaborated; it contains objectives, importance, processes and activities that facilitates teacher’s training, through steps for the correct performance in teaching, developing language skills in children. In conclusion, the use of active strategies allows the development of abilities, skills and attitudes aimed at meaningful learning, strengthening reading comprehension and critical thinking.